Hashemite Kingdom of Jordan Education Sector Public Expenditure Review - World Bank (World Bank, Washington, DC, 2018)
This education sector public expenditure review (PER) aims to respond to policy questions on the mind of the Jordanian Ministry of Education (MOE) using data readily available to the Ministry as well as common analytical techniques. Despite impressive achievements in terms of access to education, policymakers in Jordan are keenly aware of the relatively low student learning outcomes in the country. This PER uses available MOE Education Management Information System (EMIS) and Ministry of Finance (MOF) budget data, in addition to other readily available sources of data, to shed light on the performance of the Jordanian education system and address policymakers’ concerns. The EMIS currently includes data by school on numbers of teachers and students; physical attributes such as land area, buildings, and classrooms; in addition to the school’s geographic location, type, and supervising authority. The present EMIS therefore allows for relatively detailed analysis of the Jordanian schooling system, as will be shown in this report. However, the EMIS also entails shortcomings, as it does not allow for calculation of repetition and drop-out rates, for example, nor does it include any school financial data. The present report begins by describing the achievements as well as shortcomings of Jordan’s education system (Section two); Section three describes the current education learning environment, including some detail on the basic system attributes of school size, class size, and student-teacher ratio; Section four then turns to public education spending and its allocation across capital and recurrent spending, as well as the costs associated with the Syrian crisis; Section five hones in on teacher compensation in particular, given its large share in spending; and Section six provides resulting recommendations and international good practice for policymakers’ consideration.